2016
DOI: 10.1093/mnras/stw2968
|View full text |Cite
|
Sign up to set email alerts
|

Imprint of DES superstructures on the cosmic microwave background

Abstract: Small temperature anisotropies in the Cosmic Microwave Background can be sourced by density perturbations via the late-time integrated Sachs-Wolfe effect. Large voids and superclusters are excellent environments to make a localized measurement of this tiny imprint. In some cases excess signals have been reported. We probed these claims with an independent data set, using the first year data of the Dark Energy Survey in a different footprint, and using a different super-structure finding strategy. We identified… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 65 publications
4
55
0
Order By: Relevance
“…This would mean the primordial CS profile is even less significant than measured. Alternative models, which are not investigated here, may explain the slightly higher than expected causal relation between the observed and expected ISW of large voids seen in certain studies (Granett et al 2008;Cai et al 2014;Kovács et al 2017;Kovács 2017) but not all (Ilić et al 2013;Hotchkiss et al 2015;Nadathur & Crittenden 2016). Whether this is the case could be studied in future and would have implications for the predicted ISW contribution to the CS.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…This would mean the primordial CS profile is even less significant than measured. Alternative models, which are not investigated here, may explain the slightly higher than expected causal relation between the observed and expected ISW of large voids seen in certain studies (Granett et al 2008;Cai et al 2014;Kovács et al 2017;Kovács 2017) but not all (Ilić et al 2013;Hotchkiss et al 2015;Nadathur & Crittenden 2016). Whether this is the case could be studied in future and would have implications for the predicted ISW contribution to the CS.…”
Section: Discussionmentioning
confidence: 80%
“…This was recently confirmed by Mackenzie et al (2017) who observed three voids along the LOS and came to the same conclusion. Hints of a stronger than expected ISW signal have been found in some stacked void studies (Granett et al 2008;Cai et al 2014;Kovács et al 2017;Kovács 2017), leading to speculation that the causal relation between the CS and the LOS voids may be much greater than that predicted by the ISW. However, Ilić et al (2013), Hotchkiss et al (2015) and Nadathur & Crittenden (2016) have found no such excess and obtain results consistent with ΛCDM.…”
Section: Introductionmentioning
confidence: 93%
“…Another common approach in measuring the ISW signal is by stacking of voids and super-clusters. Similar to the cross-correlation method, studies using this approach have obtained detection significances ranging from low to moderate (Granett et al 2015;Kovács et al 2017), to 3σ or higher (Pápai et al 2011;Nadathur & Crittenden 2016;Cai et al 2017;Planck Collaboration et al 2016c). Interestingly, a number of these studies have reported a signal with a higher amplitude than expected based on ΛCDM predictions.…”
Section: Introductionmentioning
confidence: 99%
“…Although, the large structures (both superclusters and supervoids) found in extensive galaxy surveys, such as SDSS DR6 (Adelman-McCarthy et al 2008), seem to correlate with the CMB temperature variations, the reported amplitude of the signal (e.g. Granett et al 2008;Ilić et al 2013;Kovács et al 2017) is substantially larger than that expected for the ISW effect (e.g. Hernández-Monteagudo & Smith 2013; Hotchkiss et al 2015).…”
Section: Voids Vs Cmbmentioning
confidence: 97%